'Fear of god' as the foundation of morality in the ethical writings of medieval arabophone christian authors - İÇÖZ, AYŞE (Peeters Publishers, 2021)
Kitā
Keywords: Sosyal ve Beşeri Bilimler; İlahiyat; Dinler Tarihi; Social Sciences and Humanities; Theology; History of Religions; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; DİN; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; RELIGION; Religious Studies; Social Sciences & Humanities